Pemanfatan Media Social Untuk Meningkatkan Daya Jual Produk UKM Di Kelurahan Panorama Kota Bengkulu - Hartono, Rudi; Oktavia , Selistina (Universitas Dehasen Bengkulu, 2021)
Social media utilization has become an important strategy for Small and Medium Enterprises (SMEs) in increasing the marketability of their products in the current digital era. This study aims to assess the impact of social media utilization in increasing the marketability of SME products in Panorama Village, Bengkulu City. Through quantitative and qualitative approaches, data was collected through surveys and interviews with SME owners and social media users in the area. The results show that social media utilization has a significant positive impact on increasing the marketability of SME products. Factors such as wider market reach, more intense interaction with customers, and improved brand image are the main contributions of this strategy. The implications of this study provide practical guidance for SMEs in the region in effectively utilizing social media to improve their competitiveness and business growth in an increasingly competitive market.